THE SCIENCE OF HADITH CRITICISM (AL- JARH WA AL- TA‘DIL): A NOBLE SCIENCE FOR A NOBLE COURSE - Dutsima, Ahmad Maigari (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This study examines the science of Hadith criticism (Al-Jarh Wa Al-Ta’dlil), a crucial aspect of Islamic scholarship that deals with the evaluation and authentication of Hadith and to introduce the genesis of Hadith criticism, also to show that the science has a purpose and is one of the fundamental fields in the science of Hadith. The science aims at assessing the reporters of Hadith in order to determine whether those narrators are acceptable or not especially as it relates to Isnad, one of the two major aspects of Hadith, the other being the Matn or the text of a Hadith. The methodology that is followed is that of qualitative analysis through empirical discourses that appeal to the mind. The paper was able to make the reader find out why the scholars are partaking in this with the aim of purifying the second source of Islam, the Hadith of the most Noble Messenger, our Prophet Muhammad (may the Peace and Blessing be upon him). The also research provides a critical analysis of the methodology and applications of Al-Jarh Wa Al-Ta’dlil, highlighting its significance in ensuring the accuracy and reliability of Islamic knowledge. The study also explores the historical development of Al-Jarh Wa Al-Ta’dlil, its key principles and concepts, and its relevance to contemporary Islamic scholarship. The findings of this research contribute to a deeper understanding of the science of Hadith criticism and its role in preserving the integrity of Islamic knowledge. The paper concluded by showing that the purpose of this science was not to criticize the reporters for the sake of criticism but for a noble purpose.